Random responses : a crusade to contemporize Philippine architecture - Buensalido, John Patrick Anthony L. ([Place of publication not identifed] : [publisher not identified], 2014)
This book is about random responses (and Architecture)
Modern homes -- Getting down to business -- Warm welcomes -- Community spaces
Keywords: ARCHITECTURE